Cleavage and inactivation of alpha 1-antitrypsin by metalloproteinases released from neutrophils. - Vissers, M C (1988)
Human neutrophils, when stimulated with phorbol myristate acetate or fMet-Leu-Phe in the presence or absence of cytochalasin B, released metalloproteinases that catalytically inactivated the plasma serine proteinase inhibitor, alpha 1-antitrypsin. Inactivation, measured as loss of elastase inhibitory capacity, was accompanied by cleavage of a Mr 4,000 peptide from the COOH-terminus. Cleavage of alpha 1-antitrypsin by cell supernatants was inhibited by EDTA, o-phenanthroline, and DTT, but not by inhibitors of serine or thiol proteinases. Gelatinase and collagenase were separated from the medium of stimulated neutrophils. Both preparations cleaved and inactivated alpha 1-antitrypsin, with cleavage occurring close to the reactive center, at the Phe-Leu bond between positions P7 and P6. Cleavage by purified gelatinase was very slow and could account for only a minor fraction of the activity of neutrophil supernatants. The collagenase preparation was more active. However, the unusual cleavage site, and the ability of fMet-Leu-Phe-stimulated neutrophils to cleave alpha 1-antitrypsin without releasing collagenase, suggests that collagenase is not responsible for cleavage by the cells, which, by implication, is due to an as yet uncharacterized metalloenzyme. Our results demonstrate that by releasing metalloproteinases, neutrophils could proteolytically inactivate alpha 1-antitrypsin at sites of inflammation. This provides an alternative to the previously documented mechanism of inactivation by neutrophil-derived oxidants.